Augustine of Canterbury Converting the Anglo-Saxons: A Contribution to the Identity of the Medieval Missionary - Sas, Maksymilian (De Medio Aevo, 2013)
Augustine of Canterbury, who came from Rome to Kingdom of Kent in 597, is considered a founder of the English Church. This paper tries to describe his identity as a missionary preaching the Word to pagan Anglo-Saxons. The identity is discovered by analyzing descriptions of Augustine’s activity presented in the works of Gregory the Great and the Venerable Bede.
Keywords: Æthelberht of Kent; Anglo-Saxons; Apostle; Augustine of Canterbury; Baptism; Bede the Venerable; Christianization; Conversion; Evangelization; Kingdom of Kent; Miracles; Mission; Missionary; Pope Gregory the Great